Chloride ingress in cracked and uncracked SHCC under cyclic wetting-drying exposure. (1st July 2016) - Paul, Suvash Chandra; van Zijl, Gideon P.A.G.; Babafemi, Adewumi John; Tan, Ming Jen
Highlights: Chloride content in cracked SHCC and mortar in loaded and unloaded specimens. First publication of free and total chloride content in cracked SHCC. Rapid chloride migration test for SHCC. Relationship between total and free chloride in SHCC. Abstract: This paper reports the performance of strain hardening cement-based composite (SHCC) containing polyvinyl alcohol (PVA) fiber under chloride exposure of both cracked and uncracked specimens. The performance of SHCC was also compared to that of an identical mortar mixture without fibers. Three-point bending was applied to mechanically induce cracks in both reinforced SHCC and mortar specimens. Cracks were also formed in unreinforced SHCC specimens, whereas cracks were not formed in the unreinforced mortar specimens because of its brittle behavior. Thereafter, specimens were subjected to cyclic and continuous chloride attack for defined time periods. Both total and free chloride in SHCC and mortar specimens were then determined by means of X-ray florescence (XRF) and chemical analysis according to RILEM recommendations. Rapid chloride migration tests were also performed to determine the chloride migration coefficient in both SHCC and mortar. The results confirm that the mechanically-induced cracks in the SHCC specimens lead to higher chloride migration than in uncracked SHCC.